Implementasi Green Business pada Lahan Bekas Tambang Batubara: Studi Kasus PT. Bukit Asam Tbk - Muhamad Burhanudin; Januar Eko Prasetio; Kusharyanti Kusharyanti (Pusat Riset dan Inovasi Nasional, 2026)
This study analyzes the implementation of green business principles through productive reclamation on post-coal mining land managed by PT Bukit Asam Tbk in Muara Enim, South Sumatra. A qualitative descriptive case study approach was applied using observation, documentation, and in-depth interviews, with analysis based on the Triple Bottom Line [8] and Full Cost Accounting [11] frameworks. The results show that the development of a 1.6-hectare durian plantation successfully integrates ecological recovery with social and economic value creation. Environmentally, the project improved soil quality, enhanced biodiversity, and contributed approximately 1.92 tons of carbon sequestration per year. Socially, it generated local employment and increased community income. Economically, the project proved feasible with an NPV of IDR 1.39 billion, an IRR of 26.4%, a BCR of 2.21, and a Payback Period of 6.2 years. The application of Full Cost Accounting and GRI-based sustainability reporting enhanced corporate transparency and accountability.